The Impact of Self-Narratives of Motherhood for Mothers of Children with Autism - Trzebiński, Jerzy; Wołowicz-Ruszkowska, Agnieszka; Wójcik, Adrian Dominik (Frontiers in Psychology, 2016)
The main goal of this study was to identify the impact of a narrative construction of a life challenge - discovering to have a child with autism - on the meaning of life and on resources for coping depending on the challenge’s novelty, i.e. the number of years from the diagnosis. 364 mothers of children with autism participated in a long–term 3x2 experiment. Half of the mothers had children with autism at the age of 9–12 years. For the remaining half, having children with autism was a new and stressful life situation. Their children were 2–3 years old and just diagnosed by a medical center as having autism spectrum disorder. The mothers were assigned to one of three study conditions: they were either asked to write stories of their motherhood or to describe their children’s behavior on a questionnaire or they did not participate in any tasks. One month and then four months after this task the participants completed measures of meaning of life and several well–being scales. The results indicated that following the narrative writing the participants had the highest scores on the meaning of life and well–being scales. This affect was sustained over 4 months and was significant only for mothers with older children. The mediation analysis showed that the effects of the experimental conditions on different well–being scales were mediated by the changes in perceived meaning of life. The results suggest that construction of self–narratives of difficult ongoing challenges facilitates meaning making and subsequently strengthens resources for coping. However, it seems that a meaning-making construction of such self–story may be blocked by the uncertainty and stress caused by novelty of the challenging situation.